THE EFFECT OF INTEREST RATES AND INFLATION ON ISLAMIC STOCK RETURNS IN COMPANIES LISTED ON THE JAKARTA ISLAMIC INDEX - Cahyanti, Irni Sri; Janwari, Yadi; Solehudin, Ending; Jubaedah, Dedah (Airlangga International Journal of Islamic Economics and Finance, 2024)
This research is motivated by macroeconomic fluctuations through interest rates and inflation followed by fluctuations in Islamic stock returns. This study aims to describe and analyze: 1) The effect of interest rates on Islamic stock returns in companies listed on the Jakarta Islamic Index; 2) The effect of inflation on the return of Islamic stocks in companies listed on the Jakarta Islamic Index; 3) The effect of interest rates and inflation simultaneously on the return of in companies listed on the Jakarta Islamic Index. This research method is with quantitative types, descriptive methods of analysis and empirical juridical approaches. The samples used by 8 companies listed in the Jakarta Islamic Index for the 2016-2022 period were taken by purposive sampling techniques. Data collection techniques use documentation through secondary data and data analysis methods (Panel Data Regression). The results showed that: 1) Interest rates partially had a positive and insignificant effect on the return of Islamic shares in companies listed on the Jakarta Islamic Index; 2) Inflation partially has a positive and insignificant effect on the return of sharia shares in companies listed on the Jakarta Islamic Index; 3) Simultaneously, interest rates and inflation have an insignificant effect on the return of Islamic stocks in companies listed on the Jakarta Islamic Index.